ABO Blood Type and Urinary Bladder Cancer: Phenotype, Genotype, Allelic Association with a Clinical or Histological Stage and Recurrence Rate - Milas, Ivan; Kaštelan, Željko; Petrik, Jószef; Bingulac-Popović, Jasna; Čikić, Bojan; Šribar, Andrej; Jukić, Irena (Global Medical Genetics, 2024)
Background Previous research on connection between the ABO blood group and bladder cancer has been based on determining the ABO phenotype. This specific research is extended to the molecular level, providing more information about particular ABO alleles.Aim To investigate the impact of the ABO blood group genotype or phenotype as a risk factor for urinary bladder cancer.Materials and Methods In the case–control study, we included 74 patients who underwent surgery for a urinary bladder tumor at the Urology Clinic, Clinical Hospital Centre Zagreb, in 2021 and 2022. The control group comprised 142 asymptomatic and healthy blood donors. ABO genotyping to five basic alleles was done using a polymerase chain reaction with sequence-specific primers. We compared ABO phenotypes, genotypes, and alleles between patients and the healthy controls and investigated their distribution according to the clinical and histological stage and recurrence rate.Results No statistically significant difference was found among the groups, nor for the observed disease stages in terms of the phenotype and genotype. At the allele level, the results show a significantly lower proportion of malignancy in O1 (p < 0.001), A1 (p < 0.001), and B (p = 0.013), and a lower proportion of metastatic disease in A2 (0%, p = 0.024). We also found significantly higher proportions of high-grade tumors in patients with O1 (71.4%, p < 0.001), A1 (70.1%, p = 0.019), of nonmuscle invasive tumors in patients with O1 (55.1%, p < 0.001), O2 (100%, p = 0.045), and recurrent tumors in patients with O1 (70.2%, p < 0.001) and A1 (74.2%, p = 0.007) alleles.Conclusion We did not find an association between the ABO blood group genotype or phenotype as a genetic risk factor for urinary bladder cancer. However, an analysis at the allelic level revealed a statistically significant association between certain alleles of the ABO blood group system and urinary bladder tumors, clinical or histological stage, and recurrence rate, respectively.
Keywords: ABO blood groups; urinary bladder cancer; ABO phenotype; ABO genotype; ABO allele; case–control study